Spatial and seasonal characterization of environmental conditions in mangrove habitats occupied by Terebralia palustris in Calang, Aceh Jaya, Indonesia - MUHAMMAD FAUZAN ISMA; SLAMET B. PRAYITNO; HAERUDDIN HAERUDDIN; MAX R. MUSKANANFOLA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Isma MF, Prayitno SB, Haeruddin, Muskananfola MR. 2026. Spatial and seasonal characterization of environmental conditions in mangrove habitats occupied by Terebralia palustris in Calang, Aceh Jaya, Indonesia. Biodiversitas 27 (7): d270726. https://doi.org/10.13057/biodiv/d270726. Terebralia palustris is a large potamidid native to mangrove ecosystems, contributing to leaf litter processing and nutrient cycling within its natural habitat. The species is also recognized as a potential local food resource; therefore, studying the baseline ecological parameters of its natural habitat is important for sustainable utilization and future development. This study explores the variation of water quality, sediment properties, and litter production in mangrove areas occupied by T. palustris according to locations and seasons. Field observations were conducted in the Sayeung River, Calang, Aceh Jaya District, Indonesia, in January and August 2024, representing rainy (wet) and dry seasons, respectively. Data were collected at four stations along the estuarine gradient, with three 10 m × 10 m plots established at each station. Water and sediment physicochemical variables, sediment texture, organic carbon, total nitrogen, and mangrove litter production were measured and explored using Principal Component Analysis (PCA). Salinity ranged from 8.67 to 29.33%, while water pH ranged from 6.36 to 7.62, and sediments were dominated by sand fractions. Environmental conditions during the rainy-season were characterized by lower salinity and higher sediment organic carbon and total nitrogen, whereas dry-season showed higher temperature, salinity, pH, and Dissolved Oxygen (DO). PCA indicated that downstream habitats were associated with stronger marine influence, higher salinity, water temperature, sand fraction, and sediment redox potential, while upstream and inner-mangrove habitats were associated with organic carbon, total nitrogen, DO, sediment moisture, and finer sediment fractions. These findings show that T. palustris occupies environmentally heterogeneous mangrove habitats shaped by the interaction between tidal seawater, freshwater input, sediment composition, and organic matter accumulation. The findings provide an ecological baseline for understanding occupied habitats of T. palustris in the Calang mangrove ecosystem and for guiding future conservation, habitat monitoring, and aquaculture-related studies.